Influencing mechanism of coal miners’ safety compliance: A chain mediating model - Li, Yongzhan (Frontiers in Psychology, 2022)
The influence that job insecurity has on employees’ safety psychology and behavior has been identified in many empirical studies, but few of these examine the influencing mechanism of job insecurity on coal miners’ safety behaviors. In the de-overcapacity circumstances of coal production in China, using the strength model of self-control and conservation of resources theories, a chain mediating model was constructed to determine the relationships between job insecurity, emotional exhaustion, mind wandering, and safety compliance among coal miners. Data were collected from 447 coal miners working in three coal mines of Henan Pingdingshan Coal Industry Group. It was found that job insecurity negatively affected safety compliance, and emotional exhaustion and mind wandering played a chain mediating effect in the relationship between job insecurity and miners’ safety compliance, along three specific paths. This study helps advance the understanding of the internal mechanisms of coal miners’ job insecurity and how this affects individual safety performance. It also provides empirical evidence that managers can use effectively intervene in coal miners’ safety performance.